2021
DOI: 10.3390/biology10090847
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mutations and Non-Coding RNA-Based Epigenetic Alterations Mediating the Warburg Effect in Colorectal Carcinogenesis

Abstract: Colorectal cancer (CRC) development is a gradual process defined by the accumulation of numerous genetic mutations and epigenetic alterations leading to the adenoma-carcinoma sequence. Despite significant advances in the diagnosis and treatment of CRC, it continues to be a leading cause of cancer-related deaths worldwide. Even in the presence of oxygen, CRC cells bypass oxidative phosphorylation to produce metabolites that enable them to proliferate and survive—a phenomenon known as the “Warburg effect”. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…Cancer arises due to several genetic and epigenetic alterations [18], and many of these happen at very early stages of cancer development. Previously, we and others have reported several DNA methylation-based epigenetic changes due to H. pylori infection which could be potential therapeutic targets [13,14,19], but the diagnostic molecules were never identified.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer arises due to several genetic and epigenetic alterations [18], and many of these happen at very early stages of cancer development. Previously, we and others have reported several DNA methylation-based epigenetic changes due to H. pylori infection which could be potential therapeutic targets [13,14,19], but the diagnostic molecules were never identified.…”
Section: Discussionmentioning
confidence: 99%
“…The invasion and metastasis of OC is a complicated process, which poses difficulties for early detection, intervention, and treatment ( Tymon-Rosario et al, 2021 ; Wang et al, 2021 ). The Warburg effect is one of the recognized metabolic features of tumor cells ( Abi Zamer et al, 2021 ; Nakagawa et al, 2021 ). Active glycolysis remains a common feature of cancer metabolism, and metabolic reprogramming increases the expression of critical enzymes and, ultimately, lactate secretion.…”
Section: Future Perspectivesand Conclusionmentioning
confidence: 99%
“…Likewise, lncRNAs modulate chromatin-modifying complexes or directly interact with transcription factors to suppress translation [ 17 ]. In recent years, many studies have shown that these ncRNAs play significant roles in epigenetic modification by targeting specific gene sequences and transposons, where they exert upregulation or silencing of the gene expression to control cell differentiation [ 18 , 19 ].…”
Section: Eukaryotic Epigenetic Mechanismsmentioning
confidence: 99%